Percurso e processo de institucionalização da Educação a Distância na Universidade Federal de Mato Grosso - Petter, Rosemery Celeste (2019)
The Federal University of Mato Grosso (UFMT) has a pioneering history in the institutional insertion of Distance Education (EaD). The first licentiate degree course in this modality approved by the Ministry of Education in the country was conceived and implemented by the team of the Center for Open and Distance Education of the Institute of Education and was the locus of EaD in the institution from 1995 to 2005. In 2006, UFMT joins the Open University System of Brazil (UAB), leading to internal expansion in the offering of undergraduate and postgraduate courses Lato Sensu to other academic units. In this sense, this study’s main objective is to understand how the institutional organization of the EaD has been constituted since its insertion in the UFMT, to understand its dynamics and to analyse its process of institutionalization. This implies uncovering two questions: How has the EaD been constituted since its insertion in the UFMT, considering its normative, academic and administrative organization? Has the EaD institutional organization contributed to the institutionalization of the modality at UFMT? To this end, the theoretical framework adopted is in accordance with the definition of the concept of EaD, legal frameworks and public policies after the Law 9.394/96 of Directive and Bases of National Education, with the concepts of institutionalization and EaD institutionalization and its constituent elements. For the development of the research, the qualitative approach case study was chosen, and data collection instruments such as documentary analysis, records in archives and semistructured interviews were used to conduct the study. The results show that between 1992 and 2017, UFMT's EaD went through three phases and, throughout them, it was found that there was an effort by the institution to initiate normative and academic actions to institutionalize the modality. However, some challenges were detected in the institutionalization process, namely the low capillarization of EaD in the institution; the lack of institutional identity of the modality due to submission to the UAB model based on the form of financing; the resistance to EaD in the offering academic units due to the lack of knowledge of its specificities and restricted visibility of the modality within the institution. It is possible to conclude that in the process of institutionalization of the UFMT’s EaD, there is a need to solidify the implementation stage and to promote actions aiming to concretise the modality in the institution culture.